Seed coat development, anatomy and scanning electron microscopy of Harpagophytum procumbens (Devil's Claw), Pedaliaceae - Jordaan, A. (South African journal of botany, 2011)
Seed coat development of Harpagophytum procumbens (Devil's Claw) and the possible role of the mature seed coat in seed dormancy were studied by light microscopy (LM), transmission electron microscopy (TEM) and environmental scanning electron microscopy (ESEM). Very young ovules of H. procumbens have a single thick integument consisting of densely packed thin-walled parenchyma cells that are uniform in shape and size. During later developmental stages the parenchyma cells differentiate into 4 different zones. Zone 1 is the multi-layered inner epidermis of the single integument that eventually develops into a tough impenetrable covering that tightly encloses the embryo. The inner epidermis is delineated on the inside by a few layers of collapsed remnant endosperm cell wall layers and on the outside by remnant cell wall layers of zone 2, also called the middle layer. Together with the inner epidermis these remnant cell wall layers from collapsed cells may contribute towards seed coat impermeability. Zone 2 underneath the inner epidermis consists of large thin-walled parenchyma cells. Zone 3 is the sub-epidermal layers underneath the outer epidermis referred to as a hypodermis and zone 4 is the single outer seed coat epidermal layer. Both zones 3 and 4 develop unusual secondary wall thickenings. The primary cell walls of the outer epidermis and hypodermis disintegrated during the final stages of seed maturation, leaving only a scaffold of these secondary cell wall thickenings. In the mature seed coat the outer fibrillar seed coat consists of the outer epidermis and hypodermis and separates easily to reveal the dense, smooth inner epidermis of the seed coat. Outer epidermal and hypodermal wall thickenings develop over primary pit fields and arise from the deposition of secondary cell wall material in the form of alternative electron dense and electron lucent layers. ESEM studies showed that the outer epidermal and hypodermal seed coat layers are exceptionally hygroscopic. At 100% relative humidity within the ESEM chamber, drops of water readily condense on the seed surface and react in various ways with the seed coat components, resulting in the swelling and expansion of the wall thickenings. The flexible fibrous outer seed coat epidermis and hypodermis may enhance soil seed contact and retention of water, while the inner seed coat epidermis maintains structural and perhaps chemical seed dormancy due to the possible presence of inhibitors. ► The seed coat of Harpagophytum. procumbens is derived from only one integument. ► Unusual wall thickenings occur in the outer epidermal layer as well as in the hypodermis. ► Pectinaceous substances in wall thickenings take up moisture and are actively involved in imbibition. ► The inner epidermis contains possible inhibitors and may contribute towards dormancy. ► Due to dense cell layers, the inner epidermis may also physically restrain the emergence of the radicle.